Diversity and community composition of strictly anaerobic and culturable bacteria from the feces of Styrofoam-fed Tenebrio molitor larvae: a culturomics-based study - Zhu, Junyu; Chen, Xiaochen; Chen, Sheng-Chung; Qiu, Wanling; Yu, Jianying; Guo, Tengfei; Wang, Xianxing (Frontiers in Microbiology, 2023)
In recent years, researchers have been exploring the plastic-degrading abilities of bacteria residing in the guts of Styrofoam-eating Tenebrio molitor larvae. However, none of the reported strains have displayed highly efficient plastic degradation capabilities, and it’s noteworthy that none of the existing studies have focused on strictly anaerobic microbes. In this study, we exclusively fed Styrofoam to T. molitor larvae and examined how this dietary change influence the gut’s bacterial community composition, as observed through fecal bacteria using bacterial 16S rRNA gene amplicon sequencing and the small-scale culturomics method with 20 types of anaerobic media under four different conditions. The results revealed a significant shift in the dominant phylogroup from Lactococcus (37.8%) to Escherichia-Shigella (54.7%) when comparing the feces of larvae fed with bran and Styrofoam, as analyzing through the bacterial 16S rRNA gene amplicon sequencing. For small-scale culturomics method, a total of 226 strains of anaerobic bacteria were isolated and purified using the rolling-tube/strictly anaerobic technique. Among them, 226 strains were classified into 3 phyla, 7 classes, 9 orders, 17 families, 29 genera, 42 known species and 34 potential novel species. Interestingly, 24 genera in total, identified through the culturomics method, were not found in the results obtained from amplicon sequencing. Here, we present a collection of culturable anaerobic bacteria from the feces of T. molitor larvae, which might be a promising avenue for investigating the biodegradability of plastics by combining specific strains, either randomly or intentionally, while considering the abundance ratio of the microbial community composition.